The Students’ Anxiety in Learning English at the Eighth Grade of SMPS - Adang Ridwan; Ria Karmila (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The research focuses on the different types of anxiety experienced by students while learning English and the factors that cause this anxiety among eighth grade students at SMPS Elhafidziyah. Using a qualitative approach, this study collected data through observation and interviews, using descriptive analysis for data interpretation. The findings revealed that students in eighth grade at SMPS Elhafidziyah there are two kinds of anxiety were experienced by the students in learning English at the Eighth Grade of SMPS Elhafidziyah, they are State Anxiety, it caused students were very stressful about having to speak in front of the class and trait anxiety, the students fear and did not understand all the language. There were three factor such as factor type of task, the students felt anxious in practicing the speaking class; fear of making mistakes, most of students afraid to make mistake, the role of the language teachers.